Experimental observations on the interface front of phase change material inside cylindrical cavity. Issue 1 (29th April 2019) - Han, Xing; Kang, Zhanxiao; Tian, Xiaowei; Wang, Liqiu
Abstract: The final solidification shape of phase change material (PCM) in cylindrical cavity is important for design of thermal energy storage system. We experimentally study the role of height and radius of cylindrical cavity, Stefan number ( Ste, from 0.2000 to 0.4500), Superheating factor ( S, from 0.1250 to 0.8125). There are three main morphologies of inward solidification shape as height increases (10‐60 mm): concave, Gaussian‐distribution‐like shape and the one with a hole appearing inside PCM. The cavity radius (24‐35.5 mm) will influence the critical height of distinguishing second and third morphologies. Temperature variation during solidification process is recorded by microthermocouples, showing the main heat transfer direction. Stefan number shows significant influence to the final solidification shape while superheating factor does not. The final solidification shape of PCM can reflect the heat transfer mechanism during solidification process. Abstract : The final shape of Phase Change Material in cylindrical cavity after solidification shows Gaussian‐distribution‐like shape within certain initial height range. The final shape is influenced by the solidification boundary conditions.